Evolution of Life (Biology: The Unity and Diversity of Life) - Starr, Cecie (Brooks/Cole, Mexico, 2006)
Starr's EVOLUTION OF LIFE helps you build a foundational understanding of the history of evolutionary thought, ciroevolutionary processes, specialization, and macroevolution and shows you why it matters. Read essays on hot issues, research further, vote your position in an online poll, and then compare your votes to those of your classmates